Does winter supplementary feeding affect deer damage in a forest ecosystem? A field test in areas with different levels of deer pressure. Issue 4 (9th September 2018) - Borowski, Zbigniew; Bałazy, Radomir; Ciesielski, Mariusz; Korzeniewski, Krzysztof
Abstract: BACKGROUND: Supplementary feeding is a widespread but controversial practice in game management. While many studies have been conducted on this issue, there is limited empirical evidence on how feeding affects damage caused by wildlife. In this context, the present study focused on the effect of artificial winter feeding on tree damage in three mountain regions in Poland. RESULTS: The presence of additional winter food did not increase tree damage caused by deer in any region, as expected. Moreover, we observed that additional feeding mitigated forest damage in one region, where the highest level of deer impact had occurred. However, in this mountain region, the most important factor was elevation, which was used to classify additional feeding practice as efficient or inefficient. In the two other study regions, we did not observe any effect of supplementary feeding. CONCLUSIONS: Additional winter supplementary feeding can reduce damage caused by deer in forest stands, but only in areas with high deer pressure. Moreover, feeders should be situated in locations > 600 m above sea level in our study area. © 2018 Society of Chemical Industry Abstract : We evaluated a widespread but controversial practice in game management which is supplementary feeding. This study provides evidence that winter supplementary feeding can reduce damage caused by deer in forest stands, but only in areas with high deer pressure.